Laboratory Investigation on Roller Compaction Technique in Concrete Construction (Journal of Engineering, 2012)
Roller compacted concrete (RCC) is a concrete compacted by roller compaction. The concrete mixture in its unhardened state must support a roller while being compacted. The aim of this research work was to investigate the behavior and properties of roller compacted concrete when constructed in the laboratory using roller compactor manufactured in local market to simulate the field conditions. The roller compaction was conducts in three stages; each stage has different loading and number of passes of the roller. For the first stage, a load of (24) kg and (5) passes in each direction had been employed. For the second stage, a load of (104) kg and (10) passes in each direction were conducted. Finally, at the third stage, a load of (183) kg and (15) passes were adopted. Such procedure was in accordance to previous work conducted by the author. The effects of the type of coarse aggregate (crushed and rounded), fine aggregate (river and natural) and cement type (OPC and SRPC) on the mechanical properties of RCC were investigated. The effect of compaction method on compressive strength and indirect tensile strength was also discussed. A total of (26) roller compacted concrete slab samples of (380×380×100 mm) were prepared in the laboratory, Then, the slab specimens are taken out of the molds and immersed in the curing tank for (28) days. Core and Beam specimens were obtained from the slab samples for the determination of mechanical properties. Such properties include compressive, indirect tensile, flexural strengths using one point loading. It was concluded that the compressive strength of RCC using crushed aggregate is higher than that when using rounded aggregate in a range of (15-66) % for core specimens, while the compressive strength of RCC when using river sand is higher than that when using natural sand in a range of (9-26)% for core specimens. When river sand is implemented, RCC samples show higher indirect tensile strength than those with natural sand, such variation is within (7-8) %